Sintomatología física y mental asociada al síndrome de burnout en los profesionales de la enseñanza - Esteras, Jesús; Chorot, Paloma; Sandín, Bonifacio (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract:Physical and mental symptomatology associated with burnout syndrome in teachers.The aim of the present study was to examine the association between burnout and somatic and psychopathological symptomatology, in a sample of 171 teachers working in educational institutions (preschool, elementary school, and middle school). Participants completed the Maslach Burnout Inventory (MBI), the Somatic Symptoms Scale–Revised (Escala de Síntomas Somáticos–Revisada, ESS-R), and the Symptoms Assessment–45 Questionnaire (SA-45). Results indicate that the MBI dimension of “emotional exhaustion” is closely associated with somatic and psychopathological symptoms. Also, we found that teachers with burnout syndrome reported a higher level of (somatic and psychopathologic) symptomatology compared to non-burnout teachers. Results are discussed in relation to possible profiles associated with burnout. Key words: Burnout syndrome; teachers; somatic symptoms; psychopathological symptoms, health. Resumen:El objetivo del presente estudio consistió en examinar la asociación entre el burnout y la sintomatología somática y psicopatológica en una muestra de 171 docentes (media de edad = 39.23, DT= 11.12) que trabajaban en centros educativos (preescolar, primaria, y ESO/bachillerato). Los participantes cumplimentaron el Maslach Burnout Inventory (MBI), la Escala de Síntomas Somáticos–Revisada (ESS-R), y el Symptoms Assessment–45 Questionnaire (SA-45). Los resultados indican que la dimensión de “agotamiento emocional” del MBI se asocia estrechamente a la sintomatología somática y psicopatológica. Así mismo, se constata que los docentes con síndrome de burnout informan de mayor nivel de sintomatología (somática y psicopatológica) comparado con los docentes sin el síndrome. Se discuten los resultados en relación con los posibles perfiles asociados al burnout. Palabras clave: Síndrome de burnout; docentes; profesores; síntomas somáticos; síntomas psicopatológicos; salud.